Pendampingan Penulisan Artikel Menggunakan AI (Artificial Intellegence) bagi Guru SMP di Surabaya - Khoiri, Abdul Aziz; Suyatno; Ahmadi, Anas; Suhartono; Raharjo, Resdianto Permata (Innovative Journal of Community Engagement, 2024)
Article writing is an important skill for teachers in professional development. However, junior high school Indonesian teachers in Surabaya face many obstacles in writing articles, among the obstacles are the teachers do not know the material that can be used as articles and the teachers do not know about the latest technology that can be utilized in writing articles. This mentoring activity aims to provide services for junior high school Indonesian language teachers in Surabaya in writing articles by utilizing Artificial Intelligence (AI) technology. This activity was attended by 30 junior high school Indonesian language teachers in Surabaya, both private and public schools. The method of this mentoring activity consists of presentations, discussions, and practices in providing understanding and practical skills to junior high school Indonesian teachers in Surabaya. The results of the mentoring activities in Surabaya showed that 77.8% of the mentoring teachers did not know about articles and 66.7% of the mentoring teachers were not familiar with AI applications for article writing. In addition, the feedback results of the mentoring participants showed that the material was very suitable for the needs of the mentoring participants and the methods used during the mentoring were very effective.